Pemanfaatan Komputer dalam Pembelajaran Berbasis Augmented Reality (AR) untuk Meningkatkan Pemahaman Materi IPA di SDIT Kasih Ibu - Fikriyah, Siti Nur; Supriatna, Asep; Saepudin, Saepudin; Jaenal, Agus; Musyadad, Mia Audina (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
In this digital era, technology has an important role in improving the quality of education. This Community Service Activity (PKM) aims to increase understanding of science material at SDIT Kasih Ibu through the use of Augmented Reality (AR) technology. The main aim of this activity is to empower teachers in using AR and increase students' interest and understanding of science material. The method used is training for teachers regarding the use of AR in learning, followed by the application of this technology in the classroom. By using AR, science material is presented interactively, allowing students to more easily understand difficult concepts. The results of the activity show that teachers can implement AR well in learning. Students become more interested, active, and understand the material better, because learning is more visual and interactive. Students' digital skills also increase, because they are invited to interact directly with technology in the learning process. The implication of this activity is the importance of integrating technology in education to improve the quality of learning and students' digital skills. This activity provides an example for other schools in utilizing technology to empower teachers and improve student learning experiences. In the future, further development is needed in the use of AR and ongoing training for teachers so that the application of technology can be more optimal in learning.